Special environments: Altitude and heat - Saunders, P. U.; Garvican-Lewis, L. A.; Chapman, R. F.; Périard, J. D. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
High-level athletes are always looking at ways to maximize training adaptations for competition performance, and using altered environmental conditions to achieve this outcome has become increasingly popular by elite athletes. Furthermore, a series of potential nutrition and hydration interventions may also optimize the adaptation to altered environments. Altitude training was first used to prepare for competition at altitude, and it still is today; however, more often now, elite athletes embark on a series of altitude training camps to try to improve sea-level performance. Similarly, the use of heat acclimation/acclimatization to optimize performance in hot/humid environmental conditions is a common practice by high-level athletes and is well supported in the scientific literature. More recently, the use of heat training to improve exercise capacity in temperate environments has been investigated and appears to have positive outcomes. This consensus statement will detail the use of both heat and altitude training interventions to optimize performance capacities in elite athletes in both normal environmental conditions and extreme conditions (hot and/or high), with a focus on the importance of nutritional strategies required in these extreme environmental conditions to maximize adaptations conducive to competitive performance enhancement. Abstract from author